Review on the Vapour-Phase Synthesis of Aluminum Nitride Powder Using Thermal Plasmas - A.C.Da Cruz; R.J. Munz (KONA Powder and Particle Journal, 2014)
Production of high purity aluminum nitride powder which can be processed into electronic packages at a cost competitive with existing lower performance ceramic packages has promoted the development of many different synthesis methods. A survey of the synthesis of ultrafine AIN powders using thermal plasmas is presented. Laboratory scale experiments, applying inductively coupled and transferred-arc plasma systems, have been used to produce nanosize powders by vapour-phase reaction between aluminum vapour and ammonia, using a reduced number of steps. The specific surface area of the powders reported are in the 12 to 280 m2/g range. Sinterability experiments have demonstrated that these powders can be compacted to full density at lower temperatures than powders produced by conventional methods.